2014
DOI: 10.1089/vim.2014.0036
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses of Piglets Immunized by a Recombinant Plasmid Containing Porcine Circovirus Type 2 and Porcine Interleukin-18 Genes

Abstract: In this study, two recombinant plasmids containing the ORF2 gene of porcine circovirus type 2 (PCV2) with or without porcine interleukin-18 (IL-18) were constructed and evaluated for their ability to protect piglets against PCV2 challenge. Transient expression of the plasmids in PK-15 cells could be detected using Western blot. Piglets were given two intramuscular immunizations 3 weeks apart and were challenged with a virulent Wuzhi strain of PCV2 at 42 days after the initial immunization. All animals vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…These Qm1-related IgG sera titers for the vaccinated piglets were higher than those reported for subcutaneously vaccinated mice with a PCV2-encoding VLP-based vaccine, with a 1:40,000 titer, as well as with the CircoFLEX ® vaccine, where the titer was below 1:10,000 [26]. A DNA vaccine, expressing the Cap protein for PCV2, also showed an increase in IgG in the sera of vaccinated piglets, however, the titer was not calculated and it is therefore not comparable with the results of this work [70].…”
Section: Protection Against Pcv2 Induced By the Qm1 Antigencontrasting
confidence: 93%
“…These Qm1-related IgG sera titers for the vaccinated piglets were higher than those reported for subcutaneously vaccinated mice with a PCV2-encoding VLP-based vaccine, with a 1:40,000 titer, as well as with the CircoFLEX ® vaccine, where the titer was below 1:10,000 [26]. A DNA vaccine, expressing the Cap protein for PCV2, also showed an increase in IgG in the sera of vaccinated piglets, however, the titer was not calculated and it is therefore not comparable with the results of this work [70].…”
Section: Protection Against Pcv2 Induced By the Qm1 Antigencontrasting
confidence: 93%
“…In addition, DNA plasmid bearing PCV2 ORF2 gene has a protective effect against challenge with PCV2 in mice which could be promoted with the utilization of pIL-15.Fu [20] evaluated three adjuvants Ubiquitin (ub), the peptide binding truncated C-terminal portion of heat shock protein 70 (hsp70c) and interleukin-2 (IL-2) in PCV2 DNA vaccine, they found that ub is a superior adjuvant for PCV2 DNA vaccination than the hsp70c and IL-2 molecules. Chen [21] evaluated two recombinant plasmids containing the ORF2 gene of porcine circovirus type 2 (PCV2) with or without porcine interleukin-18 (IL-18) and found that the plasmid pBudCE4.1-ORF2/IL18 may be an effective approach for increasing the immunogenicity of PCV2 DNA vaccine.…”
Section: Discussionmentioning
confidence: 99%